2013
DOI: 10.1038/ncomms2950
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of adult-onset anaemia due to erythropoietin deficiency

Abstract: Erythropoietin regulates erythropoiesis in a hypoxia-inducible manner. Here we generate inherited super-anaemic mice (ISAM) as a mouse model of adult-onset anaemia caused by erythropoietin deficiency. ISAM express erythropoietin in the liver but lack erythropoietin production in the kidney. Around weaning age, when the major erythropoietin-producing organ switches from the liver to the kidney, ISAM develop anaemia due to erythropoietin deficiency, which is curable by administration of recombinant erythropoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(133 citation statements)
references
References 57 publications
4
129
0
Order By: Relevance
“…39), these results are consistent with NEP cell-derived Epo activating the primitive erythropoiesis at E9.0. We also found that the Cish gene, one of the early response genes to Epo stimulation 2,21 , was dramatically induced at E9.0 (Fig. 6e).…”
Section: Articlementioning
confidence: 72%
See 4 more Smart Citations
“…39), these results are consistent with NEP cell-derived Epo activating the primitive erythropoiesis at E9.0. We also found that the Cish gene, one of the early response genes to Epo stimulation 2,21 , was dramatically induced at E9.0 (Fig. 6e).…”
Section: Articlementioning
confidence: 72%
“…To elucidate the contribution of Epo to primitive erythropoiesis, we analysed an Epo-knockout (Epo-KO or Epo À / À ) mouse line ( Supplementary Fig. S1) 20,21 . No apparent abnormality was observed in Epo-KO embryos at E8.5 (5-9 somite pair stages (sp); Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations